A215 MDR3 DEFICIENCY MIMICKING WILSON DISEASE. (4th March 2021) - Flanagan, M; Little, R; Siddiqui, I; Jones, N; Ng, V
Abstract: Background: The chronic phenotype of ALF includes a broad differential diagnosis. Class III multi-drug resistance P-glycoprotein 3 (MDR3) deficiency, also referred to as progressive familial intrahepatic cholestasis type 3, is an autosomal recessive genetic disorder. It is caused by a defect on the ABCB4 gene located on chromosome 7, which encodes MDR3. MDR3 is responsible for transporting phosphatidylcholine across the canalicular membrane, thereby allowing it to be incorporated into bile micelles. MDR3 deficiency results in increased levels of free bile acids and detergent bile. Progressive cholangiopathy ensues from this detergent bile and indirectly leads to cholestasis and liver failure in severe cases. Significantly increased urinary and hepatic copper (Cu), which are hallmarks of Wilson disease, have also been reported in patients with acute hepatitis and cholestasis including patients with MDR3 deficiency Aims: We report a case of a girl who presented with a chronic phenotype of PALF, who had multiple features of Wilson disease and so was treated as such until genetic analysis confirmed MDR3 deficiency Methods Results: A 6 year old girl presented to the ED with a 1mth history of epistaxis and a 1wk history of abdominal pain and distension, facial edema, pallor and fever. Her family history was significant for parental consanguinity and maternal itch during pregnancy. On examination she had clubbing, scleral icterus and a distended abdomen with hepatosplenomegaly. Her bloodwork showed bicytopenia (HGB 53 & Plts 63) along with liver dysfunction (INR 2.9, albumin 25, conjugated bilirubin 9) and raised liver enzymes (transaminases & GGT >10xULN). Her total serum bile acids were raised at 134. An US showed hepatosplenomegaly with multiple hyperechoic nodules and perisplenic varices. She was extensively worked up for malignancy, autoimmune and metabolic disease. Serum ceruloplasmin was reduced, ophthalmology examination showed no KF rings and her 24hr urinary Cu was 10xULN. Liver Cu quantification was markedly raised at 40xULN. Liver biopsy showed cirrhosis with fibrosis related minimal non-specific portal and septal inflammation. Additionally, complete loss of canalicular staining on immunohistochemistry for MDR3 protein was noted, suggestive of MDR3 deficiency. Based on the Cu levels, a provisional diagnosis of Wilson disease was made and Cu chelation therapy was commenced pending genetic testing. A cholestatic gene panel subsequently showed homozygous pathogenic variant for the ABCB4 gene. Trientine was stopped and she was commenced on ursodeoxycholic acid. Though biochemically she remains largely unchanged, she is clinically stable whilst awaiting a liver transplant Conclusions: This case highlights the diagnostic difficulties associated with Cu test result interpretation in patients with chronic cholestatic liver disease and urges a thorough consideration of alternative diagnoses of PALF Funding Agencies: None